New Artisse intrasaccular device for intracranial aneurysm treatment: short term clinical and angiographic result from the prospective registry INSPIRE-A - Hohenstatt, Sophia; Costalat, Vincent; Dargazanli, Cyril; Killer-Oberpfalzer, Monika; Schreiber, Barbara; Rautio, Riitta; Sinisalo, Matias; Lamin, Saleh; Chew, Han Seng; Spelle, Laurent; Tomasello, Alejandro; Patankar, Tufail; et al. (Journal of neuroInterventional surgery, 2025)
Background Intrasaccular devices have broadened treatment options for wide necked aneurysms. This study presents the preliminary experience with the Artisse 2.0 device. - Methods Innovative NeurovaScular Product SurveIllance REgistry (INSPIRE) is a non-randomized, multicenter, real world clinical study with treatment arms for aneurysms (INSPIRE-A) and acute ischemic stroke (INSPIRE-S). This interim analysis included 87 patients enrolled from November 2022 to April 2024 in the INSPIRE-A Artisse cohort across 16 Europoean centers. Procedures followed standard clinical care, with 6 months of follow-up. Safety and efficacy endpoints included major stroke, neurological death, serious adverse events (SAEs), aneurysm occlusion, and retreatment rates. An independent core laboratory assessed imaging, and all SAEs were reviewed by a clinical events committee. The Artisse steering committee provided independent oversight of the data. - Results The Artisse device achieved an overall successful implantation rate of 96.6% (84/87), with satisfactory placement rates of 98.7% (74/75) for unruptured and 88.9% (8/9) for ruptured aneurysms. Following the procedure, 46.2% of unruptured aneurysm patients were receiving antiplatelet therapy (APT), predominantly aspirin monotherapy, while no ruptured aneurysm patients received APT. Device related SAE rate was 1.3% (1/87), and the overall stroke rate was 2.3% (2/87), including both ruptured and unruptured aneurysms. At 6 months, 80.0% (28/35) of patients with unruptured aneurysms showed complete obliteration, with no recurrences or retreatments. - Conclusions Preliminary experience with the Artisse 2.0 device demonstrated high technical success, favorable safety, and efficacy in aneurysm obliteration at 6 months. Larger studies with longer follow-up periods are needed to confirm these findings.
Gesehen am 22.10.2025